2016
DOI: 10.1038/ni.3419
|View full text |Cite
|
Sign up to set email alerts
|

Late stages of T cell maturation in the thymus involve NF-κB and tonic type I interferon signaling

Abstract: Positive selection occurs in the thymic cortex, but critical maturation events occur later in the medulla. We defined the precise stage at which T cells acquire competence to proliferate and emigrate. Transcriptome analysis of late gene changes suggested roles for NF-κB and interferon (IFN) signaling. Mice lacking the IKK kinase TAK1 underwent normal positive selection, but exhibited a specific block in functional maturation. NF-κB signaling provided protection from tumor necrosis factor (TNF) mediated death, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
207
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(226 citation statements)
references
References 53 publications
13
207
4
2
Order By: Relevance
“…At the SP stage, Pmel-iPSC-derived extrathymic T cells demonstrated variable expression of CD8β and CD62L relative to endogenous thymocytes, and expression of the MHC class I complex was dramatically reduced (Figures 1C and 1D). Expression of the MHC class I complex marks a developmental turning point, dividing immature thymocytes from mature, proliferation-competent SP thymocytes (Xing et al, 2016). Therefore, our results indicated that extrathymic T cells differentiated using the current OP9/DLL1 system exhibit a developmental divergence from endogenous T cells during the DP-to CD8αSP-transition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the SP stage, Pmel-iPSC-derived extrathymic T cells demonstrated variable expression of CD8β and CD62L relative to endogenous thymocytes, and expression of the MHC class I complex was dramatically reduced (Figures 1C and 1D). Expression of the MHC class I complex marks a developmental turning point, dividing immature thymocytes from mature, proliferation-competent SP thymocytes (Xing et al, 2016). Therefore, our results indicated that extrathymic T cells differentiated using the current OP9/DLL1 system exhibit a developmental divergence from endogenous T cells during the DP-to CD8αSP-transition.…”
Section: Resultsmentioning
confidence: 99%
“…To identify global transcriptional gene expression signatures, we analyzed activated signaling pathways and upstream regulators in iTEs versus extrathymic T cells using gene set enrichment analysis (GSEA) and ingenuity pathway analysis (IPA) (Figures 4D and S5A and S5B). GSEA identified enrichment of signaling pathways associated with positive selection and endogenous recent thymic emigrant (RTE) development, including the activation of IFN, nuclear factor κB (NF-κB), and TNF pathways and down-regulation of E2F signaling pathways (Figures 5A and S5A; Table S3; Carpenter and Bosselut, 2010; Xing et al, 2016). IPA showed an enrichment of similar regulatory pathways in iTEs, including activation of IFN pathway genes, as well as activation or inhibition of upstream regulators correlating to changes in activity that have been associated with late-stage thymocyte maturation (Figure S5B; Xing et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NF-kB pathway plays important roles in positive selection and postselection maturation (40,49). Moreover, many components of the NF-kB pathway have been reported to be SUMO targets (50).…”
Section: Discussionmentioning
confidence: 99%
“…These mice showed impaired production of mature SP thymocytes and failure of downregulation of CD69/HSA at the SP stage (38,39). Moreover, recently it was reported that NF-kB is involved in the late stages of T cell maturation in the thymus (40).We thus asked whether posttranslational modification or downstream target activity of these proteins was regulated by Ubc9-mediated SUMOylation pathway during positive selection. Themis, however, could not be modified by SUMO even if overexpressed together with SUMO1/2 and UBC9 in 293T cells (Supplemental Fig.…”
Section: Tcr-induced Nfat Nuclear Localization Is Regulated By Sumoylmentioning
confidence: 98%